Mode of action-specific and cause-specific retention of biologic and targeted synthetic disease-modifying antirheumatic drugs in anti-SS-A antibody-positive rheumatoid arthritis: The ANSWER cohort study - Kazuma Nishisaka; Takaichi Okano; Takumi Imai; Masanori Tsubosaka; Tomoyuki Kamenaga; Naoki Nakano; Shinya Hayashi; Wataru Yamamoto; Akira Onishi; Kosaku Murakami; Kohei Tsujimoto; Masao Katsushima; et al. (PLoS ONE, 2026)
Anti-SS-A (Ro) antibody-positive rheumatoid arthritis (RA) constitutes a clinically important subgroup, but its impact on retention of biologic or targeted synthetic disease-modifying antirheumatic drugs (b/tsDMARDs) across different modes of action (MOA) and reasons for discontinuation remains unclear. We conducted a multicenter retrospective analysis of the Japanese ANSWER cohort, including RA patients who started or switched b/tsDMARDs between 2011 and 2024 and had baseline anti-SS-A antibody testing. Among 1,452 patients (2,703 treatment courses), 255 patients (17.6%) were anti–SS-A antibody positive (507 courses, 18.8%). Propensity score matching balanced baseline characteristics, and drug retention was evaluated using Kaplan–Meier and competing risk analyses. Overall discontinuation was analyzed using Cox proportional hazards models, and Fine–Gray subdistribution hazards models were used for discontinuation by reason and for adverse event–related discontinuation stratified by MOA. After matching, 507 treatment courses from 255 anti-SS-A antibody-positive patients and 1,014 courses from 628 antibody-negative patients were analyzed. Anti-SS-A antibody positivity was not associated with overall b/tsDMARD retention (hazard ratio [HR] 1.07, 95% confidence interval [CI] 0.91–1.26, p = 0.382). In MOA-stratified analyses, positivity showed a trend toward increased discontinuation with interleukin-6 (IL-6) receptor inhibitors and cytotoxic T lymphocyte-associated antigen 4-immunoglobulin (CTLA4-Ig). In competing-risk analyses, discontinuation due to adverse events was significantly more frequent in antibody-positive patients (subdistribution hazard ratio [sHR] 1.80, 95% CI 1.28–2.52; p = 0.000685). Among adverse event-related discontinuations, anti-SS-A antibody positivity was associated with higher risks with IL-6 receptor inhibitors (sHR 2.41, 95% CI 1.24–4.71; p = 0.0098) and tumor necrosis factor (TNF) inhibitors (sHR 2.04, 95% CI 1.22–3.40; p = 0.0066), but not with CTLA4-Ig or Janus kinase (JAK) inhibitors. These findings suggest that treatment tolerability, rather than overall efficacy, may be a key determinant of b/tsDMARD survival in anti-SS-A antibody-positive RA and that MOA- and cause-specific profiles should be considered when selecting therapies in this subgroup.